The importance of hematocrit for oxygen delivery and hemodynamics - Francesco Nicosia (Emergency Care Journal, 2013)
Anemia is common in elderly patients undergoing surgery and in critical patients. A 72-year-old man submitted to a revision of hip replacement implant was diagnosed with tuberculosis, followed by pulmonary fibrosis, pulmonary heart disease and compensatory erythrocytosis. In the postoperative period, he got anemia which improved his clinical status. Anemia reduces viscosity, i.e. one of the components of vascular resistance to laminar (according to the law of Hagen-Poiseuille) and turbulent flows. In conditions of decreased hematocrit, shear thinning occurs more easily and in larger caliber vessels. Hemodiluition reduces both right and left cardiac afterloads, thus provoking an improvement of the blood flow. As the hematocrit decreases, oxygen delivery increases, because the increase in the cardiac output is greater than the decrease in the concentration of hemoglobin. Further studies are needed to confirm this physical model and to establish the variable and degree of the transfusion trigger.